Joseph Conrad and the Imperial Romance - Dryden, L. author. aut Link
XII, 228 p.
Keywords: Linda Dryden places Almayer's Folly, An Outcast of the Islands , 'Karain', and Lord Jim in the context of the nineteenth-century imperial romance. Through the thwarted dreams and aspirations of his central characters she argues that Conrad exposes the empty promises of such fiction and challenges assumptions about the superiority of European imperialists and the imperial venture itself. Using illustrations from and references to many well-known novels of Empire, Dryden demonstrates how Conrad's Malay fiction alludes to the conventions and stereotypes of popular imperial fiction.